The Asymmetric Impact of Exchange Rate Changes on Bilateral Trade between Vietnam and the US: Does the COVID-19 Pandemic Matter? - Thi, Ha Tran; Nguyen, Quang Dong; Le, Anh Duc (International Journal of Economics and Financial Issues, 2024)
This study examines the relationship between the exchange rate and the Vietnam-US trade balance by employing a combination of Autoregressive Distributed Lag (ARDL) and non-linear Autoregressive Distributed Lag (NARDL) approaches with disaggregated data from 21 industries from 2008 to 2022. The findings reveal that, in both ARDL and NARDL models, a real Vietnamese Dong (VND) depreciation does not significantly impact on the aggregated trade balance in the long-run. The results provide evidence of an asymmetric impact of the real exchange rate on the trade balance. These findings also suggest that the COVID-19 pandemic may have induced structural breaks in the relationship between exchange rates and trade balances, leading to increased sensitivity of trade balances to exchange rate movements.